Macro-anatomical Studies on the Pelvic Limb Skeleton of the Indian Mongoose (Herpestes javanicus) - A, Prasanth Babu.; V, Karunasri.; B, Supriya.; T, Sai Urmila. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The aim of the study is to document the anatomical details of bones of pelvic limb of Indian mongoose (Herpestes javanicus). Six adult Indian mongooses are collected for the present study and which died due to natural causes. The bones are collected by fresh water maceration technique. The macro-anatomy of bones of pelvic limb is studied after fresh water maceration and cleaning. The anatomy of pelvic limb bones is found to be similar in structure to the other carnivores and some rodents that have been studied. Oscoxae, the bone of pelvic girdle is sturdy and the ilium and ischium runs parallel to the vertebral column. Pelvic symphysis is formed by the pubic symphysis only. The obturator foramen is large and oval and presents a characteristic cranio-lateral notch. Fovea capitis is indistinct in femoral head; femur consists of trochanter major and minor in proximal epiphysis. Two sesamoid bones “febellae” embed in the tendons of the origin of gastrocnemius muscle. Patella is a shield shaped bone that glides over the trochlea of femur. Tibia and fibula are two long bones, articulate at proximal and distal extremities with a wide interosseous space. Seven tarsals are arranged in three rows, located between the tibia and fibula dorsally and metatarsals distally. Five metatarsal bones, I-V are evident of which first one is short. Five digits are present, first one contains two phalanges and the remaining digits contain three phalanges each. Total of eight proximal sesamoids and five distal sesamoids are present in digit region of each limb. Altogether, 46 bones are involved in the formation of one pelvic limb in Indian mongoose.